2016
DOI: 10.1002/cncr.29975
|View full text |Cite
|
Sign up to set email alerts
|

Updated results of the Gothenburg Trial of Mammographic Screening

Abstract: BACKGROUNDThere remain uncertainties about age‐specific effects of breast cancer screening on mortality due to the disease.METHODSIn 1982, a randomized trial of mammographic screening every 18 months was started in Gothenburg, Sweden. Women between the ages of 39 and 49 years were randomized to an invitation to screening (intervention group; n = 11,792) or to usual care (the control group; n = 14,321). The corresponding numbers for women between the ages of 50 and 59 years were 10,112 and 15,997. Follow‐up dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
1
26
1
Order By: Relevance
“…On the other hand, the new results of the Gothemburg trial 48 showed a statistically significant protective effect against breast cancer mortality in women under 50 years of age in long-term followup. This result is difficult to explain, precisely in a clinical trial in which there was contamination of approximately 20% of the control group during the intervention period and where more than 50% of the women aged 39 to 49 years had already received at least one mammogram at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the new results of the Gothemburg trial 48 showed a statistically significant protective effect against breast cancer mortality in women under 50 years of age in long-term followup. This result is difficult to explain, precisely in a clinical trial in which there was contamination of approximately 20% of the control group during the intervention period and where more than 50% of the women aged 39 to 49 years had already received at least one mammogram at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate the results of most randomized trials, which have shown that screening results in a decrease in the rate of advanced-stage cancer. [1][2][3][4][5] Observational studies have also looked for possible changes in the incidence of advanced-stage cancer after introducing a screening program; although early stage disease tends to have increased in these studies, advanced stage disease has variously been shown to decrease significantly, [20][21][22]37 slightly, 12,18 or not at all. 23,24,38 However, none of these studies has been able to link tumor stage to actual attendance at the individual patient level, and have instead relied on approximations.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer screening aims to reduce breast cancer morbidity and mortality by detecting disease at earlier and more treatable stages. Indeed, trials of breast cancer screening have shown that it can reduce the rate of advanced‐stage cancer, and ultimately, reduce the associated mortality . In a meta‐analysis of these randomized trials, the associated relative risk reduction was 20% .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the survival of patients with breast cancer and reduce the aggressiveness of the treatment, the early detection of the disease is extremely important. Meta-analyzes and randomized controlled trials have shown a 20-35% reduction in mortality from breast cancer due to mammographic screening [4][5][6][7]26,27 . Around 8 to 11 deaths from breast cancer will be avoided for every 1,000 women who undergo mammographic screening every two years 7 .…”
Section: Discussionmentioning
confidence: 99%